2002
DOI: 10.3354/meps235117
|View full text |Cite
|
Sign up to set email alerts
|

Density, spatial distribution and size structure of sea urchins in Florida Keys coral reef and hard-bottom habitats

Abstract: The 1983-84 Caribbean-wide mortality of the long-spined sea urchin Diadema antillarum Philippi was followed by a 2nd mortality event during 1991 in the Florida Keys. Pre-mortality sea urchin densities were up to 5 ind. m -2 and the large scale decline of D. antillarum is considered to be 1 factor affecting community dynamics of Florida Keys reefs. During 1999-2000, we surveyed 125 sites using a stratified random sampling design in shallow-water coral reef and hard-bottom habitats. Strip transects were sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1
5

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 38 publications
3
13
1
5
Order By: Relevance
“…Indeed, macroalgal values reported in this study are lower than those reported for other Caribbean reefs (Schutte et al 2010). Considering the population of D. antillarum in the Florida Keys is still well below historical levels following its mass mortality in the 1980s (Chiappone et al 2002), the protection of herbivorous fishes may have helped avert a sustained increase in macroalgae following the 1997/1998 El Niño. However, while these management actions merit recognition, macroalgal cover did not decrease at larger spatial scales during this study (Table 1).…”
Section: Discussioncontrasting
confidence: 62%
“…Indeed, macroalgal values reported in this study are lower than those reported for other Caribbean reefs (Schutte et al 2010). Considering the population of D. antillarum in the Florida Keys is still well below historical levels following its mass mortality in the 1980s (Chiappone et al 2002), the protection of herbivorous fishes may have helped avert a sustained increase in macroalgae following the 1997/1998 El Niño. However, while these management actions merit recognition, macroalgal cover did not decrease at larger spatial scales during this study (Table 1).…”
Section: Discussioncontrasting
confidence: 62%
“…McClanahan (1997) reports that macroalgal primary succession on Kenyan reefs results in a climax community reached in 120 d, generally dominated by canopy-forming brown algae under a herbivory regime dominated by fish grazing (as in the Florida Keys, where minimal recovery of the keystone grazing sea urchin Diadema antillarum [Chiappone et al 2002] yields low urchin grazing pressure). Turf-dominated climax communities were reported to develop within 50 d in conditions of intense urchin grazing or in damselfish territories (McClanahan 1997), neither of which were the case for the cyanobacterial/turf-dominated RS assemblages in the current study.…”
Section: Benthic Assemblagesmentioning
confidence: 99%
“…Diadema antillarum populations in Akumal Bay did not significantly increase from 2008-2011, which is consistent with results reported during surveys from other sites in previous years, Panama (Lessios 2005) and the Florida Keys (Chiappone et al 2002).…”
Section: Diadema Antillarum Abundancesupporting
confidence: 81%